Effects of porosity on the flow of free water surface (FWS) constructed wetland - Tan, Fibor J. (2008)
In spite of the wide use of constructed wetland in many parts of the world, parameters needed for its design is still not clearly defined. In free water surface (FWS) flow constructed wetland (CW), emergent vegetation is one of the primary wastewater treatment components. However, the presence of vegetation alters the porosity and flow pattern of water. Changes in flow patterns can have significant effect on the hydraulic residence time of HRT of the system, and thus to the removal of pollutants and treatment efficiency of CW which are a function of the HRT. Flow pattern effects of porosities on HRT as depicted in the residence time distribution (RTD) function is an important aspect in constructed wetland design.To understand the effect of porosities in an FWS constructed wetland, a 100x30x30 cm laboratory scale model tempered glass tank was set up in Chia Nan University of Pharmacy and Science in Tainan, Taiwan, R.O.C. Water level was maintained at 20cm. Porosities induced by wetland palnts (i.e. cattails(Typha spp.) in this experiment) were simulated using 22-mm diameter PVC pipes vertically secured at the bottom of the tank in a staggered array. Porosities were varied 100%, 92%, 84%, and 76% corresponding to plant densities 0 stems/m2 , 208 stems/m2, 452 stems/m2, and 603 stems/m2, respectively. Tracer tests using Rhodamine WT were conducted at flow rates of QA= 200 mL/min and QB = 600 mL/min, and QC =900mL/min corresponding to "stem Reynolds number" of Re*≈ 4.0 and below 10 and Re* >10, respectively. At these flow rates, results showed that as porosity decreases (i.e. vegetation density increases), the mean detention time (tm) decreases. This was due to displacement of the volume of water in the system caused by vegetation. However, as flow rates increased which corresponded to an increase in stem Re, change in tm becomes less sensitive to changes in porosity. It was found out that flow patterns were greatly altered by the presence of emergent artificial vegetation as exhibited by the number of tanks-in-series, N which ranged from 2.0 at higher porosities (i.e. at 100% and 92%) to 3.6 at lower porosities (i.e. at 84% and 76%). The decrease in porosity enhanced the flow pattern in an FWS CW. As the porosity of an FWS CW decreased (i.e. plant density increases), hydraulic efficiency increased. Minimum hydraulic efficiency of 0.20 was observed at 100% porosity while maximum was at 0.54 at 76% porosity.